A retrospective international study on primary extranodal marginal zone lymphoma of the lung (BALT lymphoma) on behalf of International Extranodal Lymphoma Study Group (IELSG). Issue 4 (7th July 2015) - Sammassimo, Simona; Pruneri, Giancarlo; Andreola, Giovanna; Montoro, Juan; Steffanoni, Sara; Nowakowski, Grzegorz S.; Gandini, Sara; Negri, Mara; Habermann, Thomas M.; Raderer, Markus; Li, Zhi‐Ming; Zinzani, Pier Luigi; et al.
Abstract: Primary lymphoma of the lung is a rare entity. Clinical features, optimal treatment, role of surgery and outcomes are not well defined, and the follow‐up is variable in published data. Clinical data of 205 patients who were confirmed to have bronchus mucosa‐associated lymphoid tissue lymphoma from December 1986 to December 2011 in 17 different centres worldwide were evaluated. Fifty‐five per cent of the patients were female. The median age at diagnosis was 62 (range 28–88) years. Only 9% had a history of exposure to toxic substances, while about 45% of the patients had a history of smoking. Ten per cent of the patients had autoimmune disease at presentation, and 19% patients had a reported preexisting lung disease. Treatment modalities included surgery alone in 63 patients (30%), radiotherapy in 3 (2%), antibiotics in 1 (1%) and systemic treatment in 128 (62%). Patients receiving a local approach, mainly surgical resection, experienced significantly improved progression‐free survival ( p = 0.003) versus those receiving a systemic treatment. There were no other significant differences among treatment modalities. The survival data confirm the indolent nature of the disease. Local therapy (surgery or radiotherapy) results in long‐term disease‐free survival for patients with localized disease. Systemic treatment, including alkylating‐containing regimens, can be reserved to patients in relapse after incomplete surgical excision or for patients with advanced disease. Copyright © 2015 John Wiley & Sons, Ltd.